The Subversion of the Traditional Value system Built into Language in Joyce's Portrait and Kamov's Dried Up Bog, April 1983, IASAIL (International Association for Anglo-Irish Literature)Graz, Austria - Gjurgjan, Ljiljana Ina (1983)
The text shows how on the surface Joyce's Portrait follows the traditional teleological narration, but subverts it on the metaphorical pole expressing a constant indeterminacy and reluctance. Kamov uses the same procedure in Dried-Up Bog, but in a more radical way, evidently refusing the style of the realist novel and thus creating the first existential anti-hero in Croatian literature.
ENG